2021
DOI: 10.2147/jbm.s287136
|View full text |Cite
|
Sign up to set email alerts
|

Basic Coagulation Profiles and Platelet Parameters Among Adult Type 1 and Type 2 Diabetes Patients at Dessie Referral Hospital, Northeast Ethiopia: Comparative Cross-Sectional Study

Abstract: Background Diabetes is a heterogeneous group of metabolic disorders characterized by hyperglycemia. The disease is highly associated with micro-vascular and macro-vascular complications. Thus, the main aim of this study was to compare basic coagulation profiles and platelet parameters among type 1 diabetes mellitus (T1DM), type 2 diabetes mellitus (T2DM), and healthy controls. Methods A comparative cross-sectional study was conducted at Dessie Referral Hospital from Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The prevalence of prolonged PT is lower compared to Ebrahim et al study in Ethiopia that reported a 16.7% prevalence of prolonged PT among T2DM patients. 44 Nevertheless, the prevalence of prolonged aPTT is higher compared to Ebrahim’s study that reported a 1.7% prevalence. The possible reason might be due to differences in sample size, reference range used, and the study design.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The prevalence of prolonged PT is lower compared to Ebrahim et al study in Ethiopia that reported a 16.7% prevalence of prolonged PT among T2DM patients. 44 Nevertheless, the prevalence of prolonged aPTT is higher compared to Ebrahim’s study that reported a 1.7% prevalence. The possible reason might be due to differences in sample size, reference range used, and the study design.…”
Section: Discussionmentioning
confidence: 72%
“… 54 In this study, the prevalence of thrombocytopenia is in line with Ebrahim et al study in Ethiopia that reported a 5% prevalence. 44 In addition to this, studies that are conducted in different parts of the world supported the presence of thrombocytopenia among T2DM patients. A comparative cross-sectional study conducted by Pan et al in China, 48 Madan et al in India, 55 and Asrat et al in Ethiopia 40 showed that T2DM patients were presented with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…IR can alter and upregulate gene expression pathways involving coagulation proteins, which can cause increased production of coagulation factors (including FIB, FVII, FVIII, FXII, FXIII) and fibrinogen activator inhibitor type 1 (PAI-1), resulting in a pro-thrombotic state. 23 In addition, the patients with insulin resistance have more visceral fat. 24 Visceral fat has been found to be associated with increased activity of FVII, FVIII, and FIX.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of Hussen Ebrahim et al were used to analyze the coagulation and platelet parameters [ 26 ]. Platelet parameters (platelet count, mean platelet volume (MPV), and platelet distribution width (PDW)) were analyzed using a Dirui BF 6500 automated hematology analyzer (Dirui, China) within 2 hours of sample collection.…”
Section: Methodsmentioning
confidence: 99%